Georgy Zhukov in Khalkhin-Kul and the war with the Japanese in 1939 (Journal of the College of Basic Education, 2024)
On the eve of the outbreak of World War II, battles took place that had a major impact on the conduct of battles in World War II (1939-1945). It was later called the Undeclared War. Among these battles was a battle that took place on the Mongolian-Chinese border called the Battle of Khalkhin-Kol, as it is known in the sources. Western and is known in Japanese sources as Nomanhan. As a result of this battle, Japan determined its expansionist policy. On the other hand, the battle was a real test for the Red Army. One of the most prominent leaders of the Red Army, Georgi Zhukov, emerged during the battle, and after his great victory over the Japanese army in 1939, he later became Commander of the Red Army in World War II, he achieved many military victories that contributed to the liberation of the Soviet Union from Nazi occupation and the occupation of Berlin, the German capital.